Social area influences on delinquency: a multilevel analysis - Gottfredson, Denise C. (Journal of research in crime and delinquency, 1991)
One research tradition in criminology has focused on the distribution of crime rates among social areas, and a second tradition has examined the distribution of crime among individuals. Rarely are both traditions combined in a single study. This study explores social area influences on the delinquent behavior of 3,729 adolescents who are clustered within diverse social areas. The research examines mechanisms through which the characteristics of social areas - measured independently of the characteristics of the individuals - contribute to the explanation of individual delinquent conduct. Results imply that social areas have a small effect on individual delinquent behavior. Individuals living in areas characterized by weakened family units and social disorganization report more negative peer influence and less attachment and commitment to school than do individuals living in more organized areas. Results imply that these intermediary effects produce more male aggressive crime. Females in disorganized areas also report more aggressive crimes, but the effect is only partially mediated by the theoretical intervening variables in the model. On the other hand, males living in more affluent areas report more property crimes. This area effect is present regardless of the age, race, or socioeconomic status of the respondents and is not mediated by social bonding or delinquent associates